Strategies to Create Digital Learning Materials of Early Reading for Elementary School Students Using Kodular - Hasanudin, Cahyo; Fitrianingsih, Ayu; Utomo, Dicky Nuri Prasetyo; Baihaqi, M. Abu Rizal (Universitas Muhammadiyah Surakarta, 2022)
The development of modern science and technology has to be accompanied by learning media innovation. The transformation of it can be in form of digital learning materials. The aim of this study is to investigate whether the Kodular can be utilized in compiling digital learning materials. This study is descriptive qualitative exploratory research based on depth interview in which the primary data is in form of field notes taken from interviews to the user of Kodular, the elementary school teachers, and the questionnaire results on the teachers’ needs in the elementary school. This study involves the user of Kodular and elementary school teachers which are selected using purposive sampling. The procedures of preparing digital learning materials are 1) analyzing the needs of teaching materials, 2) designing the concepts of teaching materials, and 3) developing teaching materials based on the structure of each learning material. The results of study shows that Kodular is able to be utilized in compiling digital learning materials of early reading for elementary school students by implementing Kosasih’s strategy. It can be concluded that Kodular is used as a media in compiling the materials of early reading in forms of texts, pictures, voices, and animations. The output is the digital learning materials in form of application which can be installed on Android devices.